Extrato de resíduo de goiaba como aditivo antioxidante na ração de codornas (Coturnix japônica) - Xavier, Hyara Paula Fleuri (2017)
The objective of this essay was to evaluate the use of guava extract processing as an antioxidant additive on the diet of Japanese quail matrices about the parameters on the matrices fertile performance on posture phase and the newborn quail parameters in the quality and internal health resulted from the eggs of these matrices. Three experiments were done in the School of Veterinary and Animal Science in the Federal University of Goiás (EVZ/UFG) and in all three of them, it was adopted the completely randomized design (CRD). In the first experiment, 384 Japanese quail matrices were used, 288 being females and 96 males, distributed in 4 groups, following the level of guava extract inclusion on the diet of the matrices, with a recurrence of 6 times each group, in a total of 12 females and 4 males in each recurrence. The levels of guava extract inclusion were 0,0%, 0,3%, 0,6% and 0,9%. In the second experiment, it were collected 162 eggs from each group during three days and at the end of the third day they were put in the incubator, in a total of 648 eggs. In the third experiment, 432 eggs were collected and put in the incubator in a factorial arrangement that considered two periods of preincubation storage – 216 eggs with nine days and 216 eggs with 3 days – and the four levels of guava extract inclusion on the diet of the matrices. The performance data results were submitted to the variance analysis and the quality data of the eggs were submitted to the regression analysis. The newborn quails quality parameters were submitted to the regression analysis. The hatch window were submitted to the Tukey’s test, the embryo diagnosis and the score percentage were assessed by Fisher’s exact test, the villus height analysis and intestinal crypt depth were submitted to the variance analysis. It was adopted in all the analysis 5% of probability. The use of guava extract has not influenced neither the birds’ performance nor the physicochemical quality of the eggs. In the second experiment, there was no statistical difference to the percentage of total hatch and the percentage of hatch/fertile, hatch window and the quality score of the newborn quails among the four levels of extract inclusion. The birth dispersal in the group with 0,0% of guava extract inclusion was lower than the other dispersions. 0,3% level of inclusion, the guava extract promoted improvements in the newborn quails intestinal health. In the third experiment, the guava extract inclusion was able to standardize the birth dispersal in both storage periods and promote the maintenance of the newborn quails resulted from the eggs stored for nine days. This study concludes that the use of the guava extract has not affected the matrices’ fertile performance and helped to standardize the hatch window as well as promoting intestinal health of the newborn quails.